2020
DOI: 10.4085/1062-6050-322-18
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Concussion-Assessment and Concussion-Management Practices: An Update

Abstract: Context Athletic trainers (ATs) are often the first health care providers to conduct concussion assessments and carry out postinjury management. Best practices for concussion evaluation and management have changed rapidly in recent years, outdating previous reports of ATs' concussion practices. Objective To examine ATs' current concussion-assessment and -management techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…However, if an athlete is progressing through a return to play progression as expected, it is probable appointments for clearance are made in a timely fashion. A study by Wallace and colleagues found that 84% of athletic trainers report following a gradual stepwise progression during SRC management, and the most commonly used return-to-play guidelines are the National Athletic Trainers' Association 2014 position statement and the International Conference on Concussion in Sport consensus statement 2,33. Wallace and colleagues 32 also reported an interdisciplinary approach (e.g., athletic trainers and team physician, or athletic trainers and PCP) for final return-to-play decisions is utilized 28% of the time, and 22% of the time a PCP making final return-to-play decisions alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if an athlete is progressing through a return to play progression as expected, it is probable appointments for clearance are made in a timely fashion. A study by Wallace and colleagues found that 84% of athletic trainers report following a gradual stepwise progression during SRC management, and the most commonly used return-to-play guidelines are the National Athletic Trainers' Association 2014 position statement and the International Conference on Concussion in Sport consensus statement 2,33. Wallace and colleagues 32 also reported an interdisciplinary approach (e.g., athletic trainers and team physician, or athletic trainers and PCP) for final return-to-play decisions is utilized 28% of the time, and 22% of the time a PCP making final return-to-play decisions alone.…”
mentioning
confidence: 99%
“…Wallace and colleagues 32 also reported an interdisciplinary approach (e.g., athletic trainers and team physician, or athletic trainers and PCP) for final return-to-play decisions is utilized 28% of the time, and 22% of the time a PCP making final return-to-play decisions alone. Whereas, a recent report identified team physicians (41.3%), athletic trainers (37.1%), and PCP (14.5%) as the final decision makers, with athletic trainers collaboratively involved in a majority (93.8%) of the decisions 33. Importantly, these aforementioned studies are reports of athletic trainers practicing in a variety of states and work settings, where XHSAA requires authorized clearance to be made by an MD, DO, NP, or PA.Our results suggest that in cases where student-athletes obtained clearance from an Urgent/Ready care facility, the gradual stepwise progression may have been accelerated, not monitored properly or not incorporated, resulting in the earlier clearance time.…”
mentioning
confidence: 99%
“…Os autores outrora citados, concluíram que os treinadores esportivos são membros importantes das equipes de primeiros socorros em campo, fornecendo apoio tanto aos jogadores lesionados quanto a outros profissionais de medicina esportiva. No mais, treinadores atléticos precisam melhorar a sua prática, a partir de competências próprias (exame clínico, ferramentas de avaliação padronizadas e outras) (Lempke, Schmidt & Lynall, 2020).…”
Section: Autores E Anounclassified
“…1,2 Athletic trainers play a vital role in proper concussion management because they are heavily involved in diagnosis, management, and RTP decision making. 3,4 Thus, it is imperative that ATs possess knowledge of concussions and remain up to date on concussion-assessment and -management techniques.…”
mentioning
confidence: 99%
“…These findings are valuable, but they provide limited insight into concussion practices because of the specific sample of Division I ATs, the 2011 data collection, and recently published surveys of AT practices. 3,4,18 Therefore, the purpose of our study was to examine (1) the level of concussion knowledge among ATs and (2) the influences of concussion knowledge and years of clinical experience on concussion assessment and management among ATs. We hypothesized that (1) ATs would have a generally high level of concussion knowledge and (2) those with greater knowledge and fewer years of clinical experience would be more likely to assess more concussions annually and perform recommended assessment and management techniques.…”
mentioning
confidence: 99%